Metabolic investigation and activity of Cordyceps militaris and cordycepin in cancer cell lines - Hafeez, Abdul (2023)
Inflammation is a normal reaction to infection or injury, but if the process is not resolved, it can lead to a variety of diseases, including cancer and arthritis. The available treatments for chronic inflammation are often insufficient or have unacceptable side effects, leading to a continued search for anti-inflammatory medicines with novel mechanisms of action. Natural sources are rich in anti-inflammatory compounds and are re-gaining interest. A common problem with natural medicines and natural compounds is their quality, consistency and purity. In this study, metabolomic analysis of Cordyceps militaris (L.) Fr., Cordyceps militaris extract was undertaken and thousands of compounds were identified by untargeted metabolomic analysis. Different batches from one producer were similar but had a somewhat variable cordycepin content and large differences in the cordycepin-potentiating compound pentostatin. There were much larger differences between batches from different suppliers. A comparison of the effects of cordycepin and Cordyceps extracts on inflammation in a macrophage cell line suggested that the extract contained additional activity. Untargeted metabolomics of commercially purified cordycepin (sold as 98% pure) revealed that six different batches had large numbers of significant contaminants, which were similar between suppliers. Remarkably, the batches of cordycepin differed in their cordycepin content as well as their potency. Some of the contaminants were tested in tissue culture for effects on inflammation, but many were commercially not available or even not fully identifiable. Pentostatin was also detected in cordycepin preparations. These data suggest that the reported biological activity of cordycepin may not be due to the presence of this compound alone.